Asian citrus psyllid biology, ecology and management of the Huanglongbing vector - Qureshi, Jawwad A.; Stansly, Philip A. (Philip Anzolut) (CAB International, 2020)
"This is the first book to be published which specifically focuses on Asian Citrus Psyllid and the intractable disease it spreads in citrus crops (Huanglongbing disease)"--